2019
DOI: 10.1038/s41467-018-07994-1
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature multi-phonon upconversion photoluminescence in monolayer semiconductor WS2

Abstract: Photon upconversion is an anti-Stokes process in which an absorption of a photon leads to a reemission of a photon at an energy higher than the excitation energy. The upconversion photoemission has been already demonstrated in rare earth atoms in glasses, semiconductor quantum wells, nanobelts, carbon nanotubes and atomically thin semiconductors. Here, we demonstrate a room temperature upconversion photoluminescence process in a monolayer semiconductor WS2, with energy gain up to 150 meV. We attribute this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 46 publications
10
90
2
Order By: Relevance
“…We note that during writing of the manuscript, similar results have been reported for WS 2 . The authors observe anti‐Stokes luminescence in an hBN‐encapsulated sample at temperatures as low as 7 K using high excitation powers of up to 4 mW.…”
Section: Resultssupporting
confidence: 78%
“…We note that during writing of the manuscript, similar results have been reported for WS 2 . The authors observe anti‐Stokes luminescence in an hBN‐encapsulated sample at temperatures as low as 7 K using high excitation powers of up to 4 mW.…”
Section: Resultssupporting
confidence: 78%
“…From theoretical point of view, it is well-known that obtaining numerical solutions of Bethe-Salpeter equation is computationally challenging due to poor scaling with respect to increasing mesh of k-points discretizing the first Brillouin zone 27,42 . This problem becomes even more severe when larger, experimentally relevant optical complexes [49][50][51][52] are considered in reciprocal space via generalized Bethe-Salpeter equations, e.g. for trions [53][54][55] arXiv:2001.00443v2 [cond-mat.mtrl-sci] 29 Feb 2020 and biexcitons 56 .…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from enhanced photon-exciton [26][27][28][29][30][31][32][33][34][35][36][37] and phonon-exciton interaction strength [38][39][40][41] in a low dimensional scale, as observed in graphene and V-V binary materials [42,43], TMDCs are viewed as one promising platform for exploring UC PL at the monolayer limit. And there are some research studies reporting the UC PL observed in monolayer TMDCs, for example, two-photon absorption-induced UC PL of B-exciton at 4 K [44] and phonon-mediated doubly resonant UC PL with an energy gain of 30 meV up to 250 K [45] in monolayer WSe 2 , as well as multiphonon-induced UC PL with an energy gain of 150 meV in monolayer WS 2 at room temperature [46]. However, these research studies mainly focus on the excitonic conversion mechanism during the UC PL process, and the underlying dynamical transition process and intrinsic valley properties of monolayer TMDCs are unwittingly less concerned to some extent.…”
Section: Introductionmentioning
confidence: 99%